Creative Kampong and the Promotion of Sustainable Development Knowledge in Urban Grassroots: The Case of Surakarta - Permana, Chrisna Trie Hadi; Mukaromah, Hakimatul; Astuti, Winny (Local Wisdom Jurnal Ilmiah Kajian Kearifan Lokal, 2023)
As the global trend is going into circular economy paradigm. The trend encourages business entities to focus on the production of durable, efficient, and reusable commodities to promote sustainable development. On the demand side, the market also gradually adjusts its preferences to commodities with sustainability values. With limited scale of capital, networks, and technology, Small and Medium Enterprises (SMEs) are usually lagged behind in catching new knowledge, especially those exchanged internationally. Sustainability, which is as an important knowledge under the circular economy trend, has caused serious problem for SMEs because those unable to catch the knowledge will be incompetent to serve the new market preferences and vulnerable to survive. Urban planning practices introduce the business district as one of spatial concepts to mediate the problem. It encourages enterprises with business linkages to locate next to each other and share activities and facilities. In Indonesia, the creative kampong is a local translation of business district concept, which emerges as a national hype. This research aims at studying the empirical case of the creative kampong and its knowledge transfer effectiveness for SMEs. By using the logic of Actor Network Theory (ANT) and focusing on the case study of four creative kampongs in Surakarta, we unravel the level of understanding of SMEs towards sustainability. Our data are based on stakeholder interviews and documentary reviews. The findings reveal that the majority of SMEs were understand of sustainability, and the creative kampong provided a significant contribution to ease the transfer knowledge process.